Comparative Paradigms in Early Childhood Educator Professional Development: Systematic Review and Implications for Indonesia - Lestiawati, I Made; Wiranata, I Gusti Lanang Agung; Mahendra, Made Wahyu (Studies in Learning and Teaching, 2025)
This study explores different methods of the professional development (PD) of early childhood educators (ECEs) across various countries and assesses their relevance for Indonesia. Guided by PRISMA, a systematic review synthesizes 20 international and national publications from 2014 to 2025. Four main themes emerged: global trends in ECE teacher professionalism, PD models and strategies, shifts toward transformative approaches, and contextual implications for Indonesia. The findings indicate that effective PD worldwide emphasizes ongoing coaching, collaborative learning communities, reflective practices, and the integration of digital technologies. Countries such as Finland, Singapore, Japan, Canada, and Kenya show strong systemic links between policy frameworks, teacher induction, continuous professional development, and career pathways. Based on these insights, Indonesia could adopt a hybrid model that combines top-down policy support with bottom-up, teacher-led initiatives, supported by digital platforms, professional learning networks, and child-centered reflective practices. The study underscores the importance of coherent policy design, equitable access to PD, and structured career pathways in enhancing ECE teacher professionalism. Future research should use empirical methods to evaluate hybrid PD models and examine their long-term impact on teaching quality and child outcomes.